2020
DOI: 10.1111/pan.13839
|View full text |Cite
|
Sign up to set email alerts
|

The use of prothrombin complex concentrate as a warfarin reversal agent in pediatric patients undergoing orthotopic heart transplantation

Abstract: Background Patients supported with a ventricular assist device are predisposed to severe bleeding at the time of orthotopic heart transplant due to several risk factors including anticoagulation with vitamin K antagonists. Kcentra, a four‐factor prothrombin complex concentrate, has been approved by the FDA for warfarin reversal in adults prior to urgent surgery. There is a lack of published data on the preoperative use of four‐factor prothrombin complex concentrates in pediatric patients undergoing cardiacsurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Refaai et al compared the use of prothrombin complex concentrates (PCC) with the use of FFP for anticoagulant reversal in adults and found that plasma was independently associated with volume overload (18). In addition, a small single center retrospective study by Sisti et al found that the use of PCC in pediatric patients with ventricular assist devices, for anticoagulation reversal prior to heart transplant, limited their exposure to exogenous blood products (19). Additional studies are needed to determine the best situation for each product in the pediatric population.…”
Section: Therapeutic Transfusion (Treatment Of Bleeding)mentioning
confidence: 99%
“…Refaai et al compared the use of prothrombin complex concentrates (PCC) with the use of FFP for anticoagulant reversal in adults and found that plasma was independently associated with volume overload (18). In addition, a small single center retrospective study by Sisti et al found that the use of PCC in pediatric patients with ventricular assist devices, for anticoagulation reversal prior to heart transplant, limited their exposure to exogenous blood products (19). Additional studies are needed to determine the best situation for each product in the pediatric population.…”
Section: Therapeutic Transfusion (Treatment Of Bleeding)mentioning
confidence: 99%
“…Postoperative bleeding following cardiothoracic procedures remains an important concern with multiple avenues of investigation continuing to assess factors predisposing and potentially influencing the severity of this adverse event. Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; 33 36 direct linkage of postoperative cardiac surgical bleeding with increased cost; 4 , 5 safe and efficacious use of postoperative fibrinogen concentrates; 37 , 38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39 , 40 transfusion reductions associated with the use of prothrombin complex concentrate; 41 , 42 morbidity associated with reoperation for bleeding following cardiac surgery; 3 , 43 , 44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45 , 46 contribution of albumin/gelatin to postoperative bleeding; 47 49 advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; 50 52 benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53 , 54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55 , 56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…2 Recent reports describe that in ventricular assist device-dependent pediatric patients requiring VKA reversal prior to heart transplantation, PCC receipt use was associated with decreased blood product transfusion (PRBCs, FFP, and platelets) compared with FFP. 13 Understanding rapid repletion of coagulation factors following CPB is essential for optimizing outcomes, we were not surprised to find an increasing rate of PCC utilization. However, it is important to note that data to support PCC use in pediatric cardiovascular procedures are limited to small case series in both pretransplant VKA reversal 13 and post-CPB hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…13 Understanding rapid repletion of coagulation factors following CPB is essential for optimizing outcomes, we were not surprised to find an increasing rate of PCC utilization. However, it is important to note that data to support PCC use in pediatric cardiovascular procedures are limited to small case series in both pretransplant VKA reversal 13 and post-CPB hemorrhage. 14 In post-CPB hemorrhage, there are no prospective data to support routine or prophylactic PCC use, and such use should be approached with caution.…”
Section: Discussionmentioning
confidence: 99%